Non-pharmaceutical rehabilitation of chronic heart failure patients - M. T. Kudaev; K. A. Masuev; S. Sh. Suleymanov (Российский кардиологический журнал)
Hypoxia therapy was administered to 100 patients with coronary heart disease and Functional Class I-III heart failure. Control group consisted of 50 patients. The treatment resulted in improved myocardial work capacity, coronary reserve, and quality of life.